'I will lay waste your cities, and you will become a desolation'. Insurgency and counter-insurgency in Judaea. (3rd July 2020) - Davies, Gwyn
ABSTRACT: This article examines the two major and prolonged insurgencies that the Roman empire faced in Judaea in the first and second centuries C.E. It seeks to explain the historical contexts for these conflicts and to discuss the strategies pursued by both the imperial power and its insurgent enemies. In each case, once insurrection had broken out, the Roman authorities proceeded in a methodical manner involving the concentration of maximum force to achieve the goal of suppression. On the other hand, their Jewish enemies sought out adaptive responses that took account of the overwhelming imperial strength and applied the lessons learned from the failure of the First Revolt to re-imagine the course of opposition in the Second. The use of exemplary violence as a coercive tool of policy is discussed as is the challenge of dealing with an internally fractured and factionalized population.